Experimental study on the key factors of low-loss threshing of high-moisture maize - Zhu, Xiaolong; Chi, Ruijuan; Du, Yuefeng; Qin, Jiahao; Xiong, Zexin; Zhang, Weitong; Li, Xiaoyu (International Journal of Agricultural and Biological Engineering, 2020)
The rates of maize breakage and entrainment loss are high in the harvest of high-moisture maize, which remains an issue with the development of agricultural mechanization. In order to reduce the maize breakage and entrainment loss rates, the correlations among key factors, such as the threshing cylinder speed, concave clearance and feeding rate, and the rates of breakage and entrainment loss during high-moisture maize harvesting were studied in this paper. A single-factor experiment was carried out using a single-longitudinal-axial flow maize harvester, and an orthogonal experiment was carried out using single- and double-longitudinal-axial flow maize harvesters with the Taguchi experimental design method. The single-factor experiment revealed that when the cylinder speed increased, the breakage rate of maize decreased first and then increased, while the entrainment loss rate decreased. The breakage rate of maize decreased as the concave clearance increased, while the entrainment loss rate decreased first and then increased. The optimum value of the concave clearance was positively correlated with the ear diameter of maize; Additionally, the minimum breakage rate of maize occurred when the feeding rate was at the rated value, and the entrainment loss rate increased as the feeding rate increased. The orthogonal experiments revealed that the importance of cylinder speed, feeding rate, concave clearance on the maize breakage and entrainment loss rates were in descending order. The optimum values of parameters for the single-longitudinal-axial flow maize harvester were 370 r/min cylinder speed, 40 mm concave clearance and 10 kg/s feeding rate. The optimum values of parameters the double-longitudinal-axial flow maize harvester were 550 r/min cylinder speed, 35 mm concave clearance and 10 kg/s feeding rate. The research can provide a reference for parameter configuration and control strategy for the longitudinal-axial flow maize harvester with high-moisture maize. Keywords: high-moisture maize, maize harvester, parameter configuration, Taguchi experiment DOI: 10.25165/j.ijabe.20201305.5653 Citation: Zhu X L, Chi R J, Du Y F, Qin J H, Xiong Z X, Zhang W T, et al. Experimental study on the key factors of low-loss threshing of high-moisture maize. Int J Agric & Biol Eng, 2020; 13(5): 23–31.